Evaluation of Orthodontic Patients at State and Foundation Universities According to the ICON Index - Nilüfer Yılmaz Öğütlü; Ebrahim Almahdi; Gülşilay Sayar; Hülya Kılıçoğlu (Galenos Yayinevi, 2018)
Objective:In Turkey, orthodontic treatments of individuals aged <18 years are covered by the Social Security Institution (SSI) according to the Index of Complexity, Outcome, and Need (ICON) index at contracted healthcare providers. The aim of this study was to determine treatment needs and difficulties of patients applying to orthodontic clinics in state and foundation universities in Istanbul according to the ICON and to evaluate the extent of treatment coverage by the SSI.Methods:Pre-treatment study casts of 831 patients were evaluated in terms of treatment needs and difficulties according to the ICON. This sample was distributed as 677 patients who applied to a State University's Orthodontic Department and 154 who applied to a Foundation University's Orthodontic Department.Results:At the state university, 27.9% of the 437 patients had a score of <43 and were thus, described as "no treatment needed." At the foundation university, 35% of the 154 patients had a score <43 and were thus, described as "no treatment needed." When the ICON scores of the two universities were compared, no statistically significant difference was found between treatment needs distributions.Conclusion:The number of patients who applied for treatment for the same period was three times higher in the state university than in the foundation university, whereas the rates of treatment needs were found to be similar between both state and foundation universities. At both universities, nearly one-third of patients were evaluated as "no treatment needed." The ICON index was found to be a reliable index in terms of reproducibility.